2021
DOI: 10.3390/diagnostics11050774
|View full text |Cite
|
Sign up to set email alerts
|

Variants of PCSK9 Gene Are Associated with Subclinical Atherosclerosis and Cardiometabolic Parameters in Mexicans. The GEA Project

Abstract: Background: Coronary artery disease (CAD) is a chronic, inflammatory, and complex disease associated with vascular risk factors. Nowadays, the coronary artery calcium (CAC) is a specific marker of the presence and extent of atherosclerosis. Additionally, CAC is a predictor of future coronary events in asymptomatic individuals diagnosed with subclinical atherosclerosis (CAC > 0). In this study, our aim is to evaluate the participation of two polymorphisms of the PCSK9 gene as genetic markers for developing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Our results are consistent with a recent study by Zamarrón-Licona et al in healthy individuals and subclinical atherosclerosis patients. No significant association between total plasma cholesterol and triglyceride, with PCSK9 rs615563, was found in this study, and interestingly, the rs615563 polymorphism in the control group was associated with a decreased risk of hypertriglyceridemia [ 32 ].…”
Section: Main Textmentioning
confidence: 90%
“…Our results are consistent with a recent study by Zamarrón-Licona et al in healthy individuals and subclinical atherosclerosis patients. No significant association between total plasma cholesterol and triglyceride, with PCSK9 rs615563, was found in this study, and interestingly, the rs615563 polymorphism in the control group was associated with a decreased risk of hypertriglyceridemia [ 32 ].…”
Section: Main Textmentioning
confidence: 90%
“…We adjusted all of our analyses for the key confounders such as sex, age, education, smoking status, diabetes mellitus and physical activity to attenuate the impact of selection bias. Previous studies have demonstrated that some genetic polymorphisms are associated with a higher risk of pCAD in the Mexican-Mestizo population [ 28 , 75 ]. However, we did not evaluate the interaction between genetic susceptibility and air pollution exposure on pCAD risk.…”
Section: Discussionmentioning
confidence: 99%
“…High alkaline phosphatase concentrations were defined when values were ≥75th percentile (83.00 IU/L in men and 90.25 IU/L in women). Percentile values of adiponectin and alkaline phosphatase were acquired from a representative subsample of the GEA participants [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%